2008
DOI: 10.1007/s00125-008-1064-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polymorphisms in WFS1 on prediabetic phenotypes in a population-based sample of middle-aged people with normal and abnormal glucose regulation

Abstract: Aim/hypothesis Recently, variants in WFS1 have been shown to be associated with type 2 diabetes. We aimed to examine metabolic risk phenotypes of WFS1 variants in glucosetolerant people and in individuals with abnormal glucose regulation. Methods The type 2 diabetes-associated WFS1 variant rs734312 (His611Arg) was studied in the population-based Inter99 cohort involving 4,568 glucose-tolerant individuals and 1,471 individuals with treatment-naive abnormal glucose regulation, and in an additional 3,733 treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
3
30
1
Order By: Relevance
“…A very recent GWA study confirmed with WFS1 a type 2 diabetes susceptibility gene region [13], which had been identified earlier by candidate-gene approaches [14][15][16]. Similarly to the other novel gene variants that are associated with type 2 diabetes, two previous studies suggested that WFS1 risk alleles for type 2 diabetes might be associated with impaired pancreatic beta cell function as assessed by OGTT-derived indices of insulin secretion [17,18]. However, it is unclear whether common genetic variants in WFS1 affect insulin secretion directly or secondarily via alteration of insulin sensitivity.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…A very recent GWA study confirmed with WFS1 a type 2 diabetes susceptibility gene region [13], which had been identified earlier by candidate-gene approaches [14][15][16]. Similarly to the other novel gene variants that are associated with type 2 diabetes, two previous studies suggested that WFS1 risk alleles for type 2 diabetes might be associated with impaired pancreatic beta cell function as assessed by OGTT-derived indices of insulin secretion [17,18]. However, it is unclear whether common genetic variants in WFS1 affect insulin secretion directly or secondarily via alteration of insulin sensitivity.…”
Section: Introductionmentioning
confidence: 58%
“…Although previous studies suggest that progressive loss of insulin secretion might be an important component of the phenotype which predisposes carriers of the WFS1 variant to develop type 2 diabetes [17,18], the pathogenic mechanism of impaired insulin secretion due to genetic variation in the WSF1 locus is not completely established. The highly developed endoplasmic reticulum structure of beta cells is an important factor in beta cell function, comprising production and regulated secretion of insulin to control blood glucose levels [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[93][94][95] Studies have also suggested that the WFS1 risk allele may be associated with impaired b-cell function and the progressive loss of insulin secretion may predispose carriers of the WFS1 variant to develop type 2 diabetes. 96,97 Recently, the WFS1 risk variant, rs10010131, has been shown to specifically impair GLP-1-induced first phase and second phase insulin secretion. 98 It has been suggested that this impaired response to GLP-1 decreases post-prandial insulin secretion and may influence b-cell growth and differentiation.…”
Section: Type 1 and Type 2 Diabetes And The Er Stress Connectionmentioning
confidence: 99%
“…Rare mutations in WFS1 cause Wolfram syndrome, variation in WFS1 also predisposes to common T2DM. It has been reported that WFS1 gene variants were associated with reduced insulin response to oral but not intravenous glucose [35][36][37][38][39]. WFS1 gene was associated with estimates of a decreased pancreatic -cell function among middle-aged individuals with abnormal glucose regulation [37].…”
Section: Wsf1mentioning
confidence: 98%